Crystal size distribution characterisation of Carbamazepine-saccharin co-crystal in batch cooling crystallisation - Engku Nadia, Engku Mat Nasir (2022)
Carbamazepine (CBZ) has a problem of slow rate of absorption when administered orally in which a larger dose of the drug is needed in order to be effective in treating patients. Recently, the carbamazepine-saccharin (CBZ-SAC) co-crystal has been reported to improve the solubility through solution crystallisation method. The solubility of CBZ-SAC co-crystal is mostly influenced by factors such as surface area, phase transformation, crystal size distribution (CSD), and fluid dynamics. In order to obtained the desired crystal properties, the operating parameters should be controlled in the metastable zone width (MSZW) throughout the crystallisation process. There is limited report on the CSD of CBZ-SAC co-crystal therefore, the crystal size distribution of carbamazepine-saccharin co-crystal in batch cooling crystallisation was studied. Polythermal method of cooling crystallisation was conducted to study the MSZW and CSD of CBZ-SAC co-crystal by testing with different mole ratio of SAC to CBZ, different cooling rates and different stirring speeds at various concentration of CBZ. The CBZ-SAC co-crystal were characterised by using particle size analyser, differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), Fourier transforms infrared (FTIR) and optical microscopy. The findings found that the concentration increases the crystallisation temperature, Tcryst and dissolution temperature, Tdiss also increased. The MSZW is higher for the higher CBZ concentration and stirring speed. The nucleation order, m increases as the mole ratio of SAC/CBZ increases with decreasing MSZW. The value of nucleation kinetic constant, k is found to increase with the increasing concentration for low mol ratio. Meanwhile, for slow cooling of CSD study of CBZ-SAC co-crystal, the broad CSD and larger mean crystal size is found at higher concentration of CBZ with low stirring speed. The narrow CSD and smaller mean crystal size is observed at higher stirring speed for all mole ratio and cooling rate. The CSD study of CBZ-SAC co-crystal for fast cooling also shows broad CSD with large mean crystal size and narrow CSD with small mean crystal size at higher CBZ concentration for different mole ratio and cooling rate. The characterisation analysis of DSC, XRPD and FTIR revealed that the produced solid is CBZ- SAC co-crystal Form I. Optical microscopy showed that the CBZ-SAC co-crystal Form I have the morphology of plate-like crystal. The findings obtained in the study are useful in the crystal processing, handling and storage especially in pharmaceutical industries.